Communicating Bad News: Using Role-Play to Teach Nursing Students - Carlos Laranjeira PhD, MSc, MHN; Catarina Afonso MSc, CHN; Ana Isabel Querido PhD, MSc, MHN (SAGE Publishing, 2021)
Receiving bad news can have a profound impact on a patient's physical, psychological and social well-being. Therefore, communication of bad news is an essential skill required for health professionals. A good interpersonal relationship based on trust, empathy, and respect can help the psychological adjustment to end-of-life losses. This study presents a simulation-based learning experience designed to teach communication skills to nursing students who care for palliative patients and their family members. The authors suggest adopting Gibbs' reflective cycle during structured debriefing that enables the students to move logically through the reflective process. A student-centered learning approach can promote responsibility and success in achieving the expected learning outcomes.